The importance of serum and pleural fluid level of vascular endothelial growth factor (VEGF) and VEGF fluid/serum ratio in the differential diagnosis of malignant mesothelioma-related pleural effusion - Düzköprü, Yakup; Oruç, Zeynep; Kaplan, Muhammet A.; Ülkü, Refik; Tanrıkulu, Çetin; Esmer, Derya; Bırak, Ali; Küçüköner, Mehmet; Urakçı, Zuhat; Işıkdoğan, Abdurrahman (Contemporary Oncology/Współczesna Onkologia, 2017)
Aim of the study : Vascular endothelial growth factor (VEGF) is one of the parameters that has been studied in differential diagnosis of malignant fluids. This study is aimed at evaluate applicability of serum, fluid VEGF level and fluid to serum VEGF ratio in the diagnosis of malignant pleural mesothelioma (MPM). Material and methods : The patients with pleural effusion over age of 18, between 2011 and 2015 were included in the study. They were divided into three groups: group 1 – mesothelioma patients; group 2 – other malignancies; and group 3 – benign aetiologies. Group 1 and 2 were termed as the malignant group. Fluid, serum VEGF levels, and the ratio of fluid/serum VEGF level were studied to evaluate the fluid/serum VEGF ratio in all groups. Results : Twenty cases with mesothelioma, 44 cases with other malignancies, and 20 cases with benign aetiologies were included in this study. No statistically significant difference was found according to serum VEGF levels for all groups, (group 1: 437 ±324 pg/ml, group 2: 354 ±223 pg/ml, group 3: 373 ±217 pg/ml, p = 0.836), while fluid VEGF levels showed a statistically significant difference (group 1: 3359 ±700 pg/ml, group 2: 2175 ±435 pg/ml, group 3: 1092 ±435 pg/ml, p = 0.041). The ratio of fluid to serum VEGF levels showed a difference, at the significance limit, between the malignant (group 1 and group 2) and benign (group 3) groups (8.83 ±1.29 vs. 4.57 ±1.07, p = 0.059) but showed a statistically significant difference between the mesothelioma and benign groups (12.11 ±1.68 vs. 4.57 ±1.07, p = 0.044). Conclusions : The VEGF fluid/serum ratio may be an applicable parameter in the differential diagnosis of malignant fluids, especially MPM.